2018
DOI: 10.1101/469668
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Precisely control mitochondria with light to manipulate cell fate decision

Abstract: Mitochondrial dysfunction has been implicated in many pathological conditions and diseases. The normal functioning of mitochondria relies on maintaining the inner mitochondrial membrane (IMM) potential (a.k.a. ΔΨ m ) that is essential for ATP synthesis, Ca 2+ homeostasis, redox balance and regulation of other key signaling pathways such as mitophagy and apoptosis.However, the detailed mechanisms by which ΔΨ m regulates cellular function remain incompletely understood, partially due to difficulty of manipulatin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 63 publications
2
14
0
Order By: Relevance
“…There are several techniques that allow experimental modulation of the PMF, but most are pharmacologic and therefore irreversible and not cell‐ or tissue‐specific. Herein, we take a novel approach to overcome these barriers to precisely control the PMF by using optogenetics, adapting an approach used recently to dissipate the PMF . One family of widely used optogenetic proteins are bacteriorhodopsin‐related light‐activated proton pumps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several techniques that allow experimental modulation of the PMF, but most are pharmacologic and therefore irreversible and not cell‐ or tissue‐specific. Herein, we take a novel approach to overcome these barriers to precisely control the PMF by using optogenetics, adapting an approach used recently to dissipate the PMF . One family of widely used optogenetic proteins are bacteriorhodopsin‐related light‐activated proton pumps.…”
Section: Introductionmentioning
confidence: 99%
“…These proteins pump protons across membranes in response to specific wavelengths of light and are often used to study physiology by modulating electrochemical gradients at the plasma membrane . Only recently have precise optogenetic techniques been applied to compartmentalized cellular events using light‐activated proteins targeted to organelles [,, preprint: ,]. Rather than using a non‐specific cation channel to permeabilize the IM and dissipate the PMF, here we target the light‐activated proton pump from the fungal organism Leptosphaeria maculans to mitochondria and selectively increase the PMF.…”
Section: Introductionmentioning
confidence: 99%
“…Targeting was through N-terminal fusion to 4 repeats of the well-characterized 29 amino acid COX8A MTS (116 amino acids total) [52,58,59]. Our laboratory has found that targeting approaches using a single COX8A targeting sequence are insufficient to direct ChR2 or proton pumps to mitochondria and result instead in plasma membrane targeting, a finding that has been corroborated by others [52,60]. Mitochondrial targeting using the COX8A repeated sequence was achieved only after deleting a small leading section of the ChR2 sequence (24 amino acids) thought to contain a plasma membrane targeting sequence [52].…”
Section: Mitochr2mentioning
confidence: 64%
“…Another approach to selectively dissipate the PMF again targeted ChR2 to mitochondria using a different strategy. Similar to initial targeting strategies for mitoChR2 [52], ChR2 did not reach mitochondria using one, two, or three repeats of the COX8A MTS [60]. ABCB-ChR2 was successfully targeted using the large transmembrane ABCB10 MTS [65].…”
Section: Abcb-chr2mentioning
confidence: 84%
See 1 more Smart Citation